Books to bytes library and information technology in the new millenium: essays in honour of Prof. L S Ramaiah - Ramaiah, L S; Jagga Rao, N V; Ramchander, M (New Delhi Ess Ess, 2000)
This book provides a mine of information on various facets of library and information tecbnology.This volume containing 40 articles covering every aspect of library and presenting a vision for new milliennium. A reading of this volume provides the present
Keywords: Information technology; Library science; Digital library; Library legislation; Internet (Computer network)